Five practices of fruitful congregations - Schnase, Robert C., 1957- (Abingdon Press, 2007)
Schnase contends that successful congregations often have certain characteristics in common. These fundamental practices demonstrate congregational health, vitality, and fruitfulness. They also help churches fulfill their mission to make disciples of Jesus Christ for the transformation of the world. The five practices of fruitful congregations: Radical Hospitality, Passionate Worship, Intentional Faith Development, Risk-Taking Mission and Service, Extravagant Generosity.